Inside Cover: Bicyclic Peptide Inhibitor of Urokinase‐Type Plasminogen Activator: Mode of Action (ChemBioChem 16/2013). Issue 16 (25th October 2013) - Roodbeen, Renée; Paaske, Berit; Jiang, Longguang; Jensen, Jan K.; Christensen, Anni; Nielsen, Jakob T.; Huang, Mingdong; Mulder, Frans A. A.; Nielsen, Niels Chr.; Andreasen, Peter A.; Jensen, Knud J.
<x xml:space="preserve">Abstract</x> The inside cover picture shows the binding of a rationally designed bicyclic peptide inhibitor to the serine protease urokinase‐type plasminogen activator (uPA). On p. 2179 ff., K. J. Jensen et al. describe how a monocyclic peptide was transformed into a bicyclic peptide without loss of inhibitory properties but, rewardingly, with a reduced loss of entropy upon binding.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>